2018
DOI: 10.1177/1055665618768541
|View full text |Cite
|
Sign up to set email alerts
|

Speech in 5-Year-Olds With Cleft Palate With or Without Cleft Lip Treated With Primary Palatal Surgery With Muscle Reconstruction According to Sommerlad

Abstract: Speech was poorer in many children with more extensive clefts. Children with CP±L had poorer speech compared to normative data of peers without CP±L, but the results indicated relatively good speech compared to speech of children with CP±L in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 29 publications
4
28
0
Order By: Relevance
“…Others have published on the Sommerlad soft palate repair technique (Andrades et al, 2008; Becker & Hansson, 2013; Doucet et al, 2013; Luyten et al, 2013; 2014; Yang et al, 2013; Cairns et al, 2014; Moar et al, 2016; Rossell-Perry et al, 2015; Dissaux et al, 2016; Nyberg et al, 2018; Bruneel et al, 2018; Klinto et al, 2018; Mapar et al, 2019; Smyth & Wu, 2019). In 3 studies, the Sommerlad intravelar veloplasty was part of a protocol of delayed hard palate closure (Doucet et al, 2013; Dissaux et al, 2016; Klinto et al, 2018 [in 2 of 3 centers]); in another 2 studies, gold standard speech methodology was not used (Andrades et al, 2008; Yang et al, 2013); in 3 studies detailed speech results were not given (Becker & Hansson, 2013; Rossell-Perry et al, 2015; Moar et al, 2016). The Luyten et al (2014) study is subject to bias due to different surgeons in different countries and different languages of the speech and language therapists and participants (Hutters & Henningsson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Others have published on the Sommerlad soft palate repair technique (Andrades et al, 2008; Becker & Hansson, 2013; Doucet et al, 2013; Luyten et al, 2013; 2014; Yang et al, 2013; Cairns et al, 2014; Moar et al, 2016; Rossell-Perry et al, 2015; Dissaux et al, 2016; Nyberg et al, 2018; Bruneel et al, 2018; Klinto et al, 2018; Mapar et al, 2019; Smyth & Wu, 2019). In 3 studies, the Sommerlad intravelar veloplasty was part of a protocol of delayed hard palate closure (Doucet et al, 2013; Dissaux et al, 2016; Klinto et al, 2018 [in 2 of 3 centers]); in another 2 studies, gold standard speech methodology was not used (Andrades et al, 2008; Yang et al, 2013); in 3 studies detailed speech results were not given (Becker & Hansson, 2013; Rossell-Perry et al, 2015; Moar et al, 2016). The Luyten et al (2014) study is subject to bias due to different surgeons in different countries and different languages of the speech and language therapists and participants (Hutters & Henningsson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In PCC-A, ageappropriate simplifications of /s/ and passive cleft speech characteristics marked with diacritics (e.g. audible nasal air leakage, nasal realization and weak articulation) were scored as correct [12,29].…”
Section: Analysis Of Transcriptionsmentioning
confidence: 99%
“…The rate of pharyngeal flaps performed before 5 years of age varied between 0 and 23% [2]. In earlier Swedish studies, 18-40% of the 5-year-olds with UCLP have been reported with moderate to severe hypernasality and 0-17% had a history of secondary VPI surgery [12,[14][15][16].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations